IEDM Technical Digest. IEEE International Electron Devices Meeting, 2004.
DOI: 10.1109/iedm.2004.1419085
|View full text |Cite
|
Sign up to set email alerts
|

Physical model of BTI, TDDB and SILC in W02-based high-k gate dielectrics

Abstract: The microscopic mechanism of the degradation occurring in HQ-based high-ML dual layer gate insulator bas been investigated. The hole-injection-induced release of hydrogen from Si-H terminations causes IL-breakdown. This mechanism accelerates NBTI. Defects due to electron-trapped oxygen vacancies are the origin of trap-assisted tunneling, causing SILC in the electron current and PBTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 5 publications
4
59
0
Order By: Relevance
“…This is because the damage induces increased oxygen-vacancy-related defects, capturing electrons in oxygen vacancies within high-k film during PBTI stress. The increased degradation exhibited by damaged high-k/metalgate transistors shown in this study is consistent with PBTI physical models demonstrated in previous literatures [12,28,29]. The time exponent of the DV TH shift in damaged and undamaged transistors is identical, because the increased DV TH of these transistors are all dominated by electron trapping in the oxygen vacancies within high-k film during PBTI stress [12,22].…”
Section: Damage-enhanced Pbti Degradation For High-k/metal-gate Nmosfetssupporting
confidence: 90%
See 1 more Smart Citation
“…This is because the damage induces increased oxygen-vacancy-related defects, capturing electrons in oxygen vacancies within high-k film during PBTI stress. The increased degradation exhibited by damaged high-k/metalgate transistors shown in this study is consistent with PBTI physical models demonstrated in previous literatures [12,28,29]. The time exponent of the DV TH shift in damaged and undamaged transistors is identical, because the increased DV TH of these transistors are all dominated by electron trapping in the oxygen vacancies within high-k film during PBTI stress [12,22].…”
Section: Damage-enhanced Pbti Degradation For High-k/metal-gate Nmosfetssupporting
confidence: 90%
“…The SILC increases as the PID enhances defect generations, as well as trap associated tunneling in high-k film. Furthermore, based on previous studies [28,29], it has been proposed that the charge state of oxygen vacancies could describe the energy signature of these traps and is responsible for the increase in SILC.…”
Section: Damage-enhanced Oxygen-vacancy-related Defects Generation Anmentioning
confidence: 99%
“…They have a different energy for trapping and for de-trapping; this behavior is called a U-traps behavior in the literature and can be associated to some energy relaxation of the trap environment [17][18][19]. Their number is proportional ($1/10) to the whole trap number which is measured in dynamic condition (Fig.…”
Section: Case Of Full De-trapping At Negative V G Biasmentioning
confidence: 99%
“…Note that the electron trap must correspond to V -, not V + , as assumed by others. 11,12 The previous calculations of the oxygen V 0 levels in ZrO 2 and HfO 2 by Foster 9,10 placed the levels at 2.1 and 2.9 eV above the oxide VB edge. This low value is fundamentally because of their LDA correction method, which tied the vacancy levels to the VB as the gap was opened up from 3.5 to 5.5 eV.…”
mentioning
confidence: 97%